3G Handy Guide acting and TV presentation - 3G E-learning LLC (3G Handy Guide)
Acting, in its simplest form, is playing a role that is not your true character. Acting has been around for a long time, and art itself has a tendency to evolve over time. Artists have been breaking the traditional boundaries of what has been expected of them since Michelangelo and Picasso. The same is true of acting, so that performances can be achieved by different means because of the ever-changing cultural atmosphere. The acting profession has seen some positive developments in recent times. While many trained theater artists are trying to live off stage productions, the emerging Home Video Industry and private television stations provide opportunities for exhibitions of acting professionalism. In this guide, we will take a critical look at the essence of the act and its demands on the prospective performer. We will do this by analyzing the peculiarities of stage and screen acting. The essence of this is to create awareness that the medium has an impact on the approach. Unless the program is presented attractively, given the presentation techniques, good material and well written scripts will not have the desired impact. The presenters are members of the broadcasting company and serve as connections between the organiza-tion and the listeners. A successful presentation takes into account the aims of the show, the needs of the listener and a thorough understanding of the strengths and examples of the medium. A strong presentation addresses all the questions of the audience. Unlike television, only radio is heard in which neither the presenter nor the listener is visible. The presenter must create the illusion that he / she is with the listener, and that he / she is' talking' to him / her through voice, manner and style. Innovation, creativity, freshness and novelty are the main pillars on which the skill of presentation is built. The elements of rich vocabulary, information, knowledge and the ability to discern as to what to say and what not to say make these pillars strong and sturdy. An overall knowledge of broadcasting system stands the present-er in good stead. However, modernization, globalization and economic ambitions have contributed to a sea-change in their mindset, desires and demands.